Novel implications of a strictly monomorphic (GCC) repeat in the human PRKACB gene - Khamse, Safoura; Jafarian, Zahra; Bozorgmehr, Ali; Tavakoli, Mostafa; Afshar, Hossein; Keshavarz, Maryam; Moayedi, Razieh; Ohadi, Mina (Scientific reports, 2021)
PRKACB (Protein Kinase CAMP-Activated Catalytic Subunit Beta) is predominantly expressed in the brain, and regulation of this gene links to neuroprotective effects against tau and Aβ-induced toxicity. Here we studied a (GCC)-repeat spanning the core promoter and 5′ UTR of this gene in 300 human subjects, consisting of late-onset neurocognitive disorder (NCD) (N = 150) and controls (N = 150). We also implemented several models to study the impact of this repeat on the three-dimensional (3D) structure of DNA. While the PRKACB (GCC)-repeat was strictly monomorphic at 7-repeats, we detected two 7/8 genotypes only in the NCD group. In all examined models, the (GCC)7 and its periodicals had the least range of divergence variation on the 3D structure of DNA in comparison to the 8-repeat periodicals and several hypothetical repeat lengths. A similar inert effect on the 3D structure was not detected in other classes of short tandem repeats (STRs) such as GA and CA repeats. In conclusion, we report monomorphism of a long (GCC)-repeat in the PRKACB gene in human, its inert effect on DNA structure, and enriched divergence in late-onset NCD. This is the first indication of natural selection for a monomorphic (GCC)-repeat, which probably evolved to function as an “epigenetic knob”, without changing the regional DNA structure.